Studying the C1772T polymorphism of Hif-1Î± and TGF-Î²3 IVS5+104 A/G polymorphism in children with congenital non-syndromic neural tube defects and their mothers - Yildirim, ć°brahim Halil; Koçak, Nadir (Cellular and Molecular Biology, 2018)
Prevalence of neural tube defect (NTD) has reduced after folic acid intake. However; which mechanisms are effective in NTD are not known exactly. In this study; due to the possible effects on hypoxic pathway and embryonic development, particularly on extracellular matrix components, Hif-1Î± Pro582Ser and TGF-Î²3 IVS5+104 A/G SfaN1 polymorphisms were studied by PCR-RFLP method both on children with NTDs and mothers. Statistical differences were seen for Hif-1Î± and TGF-Î²3 IVS5+104 A/G SfaN1 polymorphisms in children with NTDs but no difference was seen in mothers. Both genes are effective on many pathways and our results suggest that regulation of extracellular matrix components of children during fetal life is important in neural tube defects formation. The results of this study show that Hif-1Î± Pro582Ser and TGF-Î²3 IVS5+104 A/G SfaN1 polymorphisms may play a role in NTDs.